FRP Composites Nano-Modified with Graphene Derivatives for Enhanced Mechanical Properties - Garg, Dhruv (My University, 2022)
The study influence of the graphene oxide (GO) inclusion on the mechanical properties of carbon fiber reinforced polymer (CFRP) hybrid composite and glass fiber reinforced polymer (GFRP) is reported. Different wt.% content of GO used for development of epoxy matrix and GFRP/CFRP hybrid composite was prepared using VARIM. GO was synthesized from graphite powder and was mixed with epoxy resin. Three different GO/rGO concentration of 0.1, 0.2, and 0.3 phr were incorporated in the GFRP and CFRP laminates. The overall performance of GFRP/CFRP laminates in which the epoxy is nano reinforced with graphene derivatives is to be assessed and the results have significantly shown that inclusion of graphene derivatives improves the mechanical properties of the composites. The performance includes tensile testing, flexural strength, and impact strength. The epoxy used in these laminates for repairing and retrofitting of the structure is of very brittle nature hance, to make the epoxy ductile nano particles, nano clay, graphene derivatives were nano reinforced on the composites. In our study, we have primarily focused on graphene derivatives i.e., graphene oxide (GO) and reduced graphene oxide (rGO) fabricated on glass and carbon fibers. It was observed that GO is improving and enhancing the strength better than rGO because of more functional groups present in their composition.
Keywords: GFRP; CFRP; Graphene; reduced graphene oxide; impact; tensile; flexural